SENSITIVITY ANALYSIS OF ACTUARIAL ASSUMPTIONS: THE CASE OF AN RPPS PARAIBANO - Bezerra, Arthur Mauricio Rodrigues (2023)
Objective: To analyze the impact of variations in actuarial assumptions on the normal cost and mathematical provision of a benefit plan offered by a Municipal Social Security Scheme. Basis: In social security entities, the manager needs to measure the plan's obligations regarding the payment of benefits. To this end, actuarial assumptions are adopted, establishing the cost plan for the respective plan. Method: A database was used relating to 2001 participants in a pension plan offered by a municipal RPPS. The plan's obligations were calculated and compared using the Projected Unit Credit costing method, varying the following actuarial assumptions: general mortality table, actuarial interest rate, salary increment and retirement postponement time. Results: The premise that most impacts the normal cost and the mathematical provision is the interest rate, followed by the postponement of retirement. Furthermore, it was found that the effect of joint variation of premises is smaller than the sum of the effects of individual variations. Contributions: The observation that postponing retirement has a major impact on plan obligations, only smaller than the impact of the interest rate.